(untitled) (The Pakistan Development Review, 1991)
Prolonged breastfeeding, apart from being beneficial to the child’s health, helps in keeping the binh rate low. One of the effects of malnutrition in developing countries is the Teduction in the period of lactation. In Pakistan, where the binh rate is already very high and the use of contraceptives limited, any reduction in the breastfeeding period may result in an increase of the binh rate. This study was undertaken to fmd out the recent changes in the breastfeeding pattern and their potential impact on the fertility levels in Pakistan. The data for this study is based on two National Fertility Surveys - the 1975 PakistBn Fertility Survey (PFS) and the 1979 Population, Labour Force, and Migration Survey (PLM). The estimation of the mean duration of breastfeeding is based on a measure developed by mosley (1982), given by the formula Y = BIN, where Y = estimate of duration of breastfeeding, B = total number of children currently being breastfed, N = the average number of binhs per mOhth. Taking mother’s age, parity, place of residence, education, and occupation as background variables, the findings are as follows: (1) a decline of about 4 months occurs in the average length of lactation; (2) age of mother is positively associated with the duration of breastfeeding; (3) urban women have shorter periods of breastfeeding; (4) women working on farms have longer periods of breastfeeding; (5) a slight increase in fertility is due to the decline in breastfeeding and the decrease in the use of contraceptives. It is suggested that breastfeeding may be promoted among Pakistani mothers to reduce the binh rate.